2023
DOI: 10.1097/inf.0000000000004019
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infections and Clinical Outcomes Among Febrile Infants up to 90 Days Old With SARS-CoV-2 Infection: A Multicenter Cohort Study

Abstract: We present a large, multicenter, cohort study that aimed to assess bacterial infection rates among febrile infants up to 90 days old presenting to the pediatric emergency department with severe acute respiratory syndrome coronavirus 2 infection during 2021–2022 throughout successive variant waves. Overall, 417 febrile infants were included. Twenty-six infants (6.2%) had bacterial infections. All bacterial infections consisted of urinary tract infections, and there were no invasive bacterial infections. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A small patient series of infants admitted to the hospital reported that two of 18 patients had a secondary late bacterial infection [ 26 ]. For infants seen in emergency departments, secondary bacterial infections were not detected in any patient at the same time or bacterial infections were not seemingly secondary as COVID-19-related complications [ 53 , 81 , 133 ]. A similar study reported no significant difference in frequency of secondary infections when infants presented with versus without COVID-19 [ 60 ].…”
Section: Controversy Regarding Infantsmentioning
confidence: 99%
“…A small patient series of infants admitted to the hospital reported that two of 18 patients had a secondary late bacterial infection [ 26 ]. For infants seen in emergency departments, secondary bacterial infections were not detected in any patient at the same time or bacterial infections were not seemingly secondary as COVID-19-related complications [ 53 , 81 , 133 ]. A similar study reported no significant difference in frequency of secondary infections when infants presented with versus without COVID-19 [ 60 ].…”
Section: Controversy Regarding Infantsmentioning
confidence: 99%